Does urinary metabolite signature act as a biomarker of post-stroke depression? - Cai, Wa; Wang, Xia-Fei; Wei, Xi-Fang; Zhang, Jing-Ruo; Hu, Chen; Ma, Wen; Shen, Wei-Dong (Frontiers in Psychiatry, 2022)
Background: The precise diagnosis of post stroke depression (PSD) is difficult to conduct in clinical practice due to complex psychopathology of depressive disorder. Several researches showed that urinary metabolite biomarkers identified by GC-MS-based approach could significantly distinguish PSD from stroke survivors. Methods: A systematic review was performed for the keywords of ‘urinary metabolite’ and ‘post stroke depression’ using Medline, Embase, Cochrane library, Web of science, PsycINFO, CNKI, Wanfang, CBM, and VIP database from inception to March 31, 2022. Results: Four related studies were included in the review. Differential urinary metabolites including azelaic acid, lactic acid, palmitic acid and tyrosine were identified in all the included studies. As significant deviation in metabolite biomarker panel, azelaic acid, glyceric acid, palmitic acid, phenylalanine, pseudo uridine and tyrosine were found in at least 2 included studies, which indicated good potential for the differentiation of PSD. Conclusion: The systematic review provided evidence that differential urinary metabolites analyzed by GC-MS-based might be used as a biomarker for the diagnosis and prognosis of PSD.